Pengaruh Infrastruktur SDN Mulyajaya 1 Karawang terhadap Pembelajaran Siswa - Zaydan, Muhamad Yaseer; Rahayu, Cantika Tresna; Nadapdapt, Cindy Debora Bestaida; Hutajulu, Dian Anggi Rahayu Kurnianingsih; Suprobo, Farrel Rajendra; Faqih, Muhammad Zibran; Dihati, Nayara; Syahputra, Rifky Jucticyo; Ramadhani, Sinta; Lubis, Yasmin Arinda (Indonesian Journal Publisher, 2024)
Equitable development is one of the pillars that lead to a golden Indonesia 2045. Equitable development in the aspect of education is the main key for a country to excel in global competition. Education is considered the most strategic field for realizing national welfare. Therefore, students' comfort in learning and ease of access to education must be guaranteed because this is the first step in helping to realize national welfare. Many factors can affect a student's learning outcomes, one of which is inadequate infrastructure. This research aims to explore the influence of infrastructure on student learning continuity. This research uses a qualitative approach with a descriptive method. Data was collected using interview and observation techniques. The results show that infrastructure is indeed proven to affect student learning outcomes and in realizing equitable development in this aspect of education there are still challenges that continue to arise, such as lack of funding. Therefore, this study recommends that the central government can focus the state budget in terms of education budget to equalize access to education in Indonesia and realize the creation of national welfare and a superior golden generation.